The Exodus as negotiation of identity and human dignity between memory and myth - Bosman, Hendrik Ludolph (HTS teologiese studies, 2014)
The rendition of the exodus in the Old Testament is an excellent example of cultural memory – a remembered past that resulted in collective memories that maintained the actuality or relevance of the past, without getting bogged down in the never ending agonising about the supposed ‘historical factuality’ of the past. In the Old Testament the exodus was remembered in diverging ways in different contexts and the ongoing need for identity and the influence of trauma were but two factors that influenced the manner in which the exodus was recalled. Despite unfavourable connotations it is again suggested that the exodus functioned as a founding myth in the evolving of Israelite and early Jewish identity. Such a heuristic goal will be less interested in establishing historically or archaeologically verifiable truth claims and more interested in how the memory of the exodus shaped identity and enabled human dignity in subsequent contexts of human suffering and oppression up to the present day.